Size-exclusion liquid chromatography for effective purification of amphiphilic trinuclear gold(I) pyrazolate complex - Mohamad Azani Jalani; Leny Yuliati; Siew Ling Lee; Hendrik Oktendy Lintang (Penerbit UTM Press, 2024)
Column gravity chromatography suffered from several drawbacks such as time-consuming and need a large amount of eluents. Herein we reported an efficient technique for effective separation of amphiphilic trinuclear gold(I) pyrazolate complex ([Au3Pz3]C10TEG) with high polarity based on size-exclusion principle of chromatographic technique. Based on the size-exclusion limit, [Au3Pz3]C10TEG having a larger size with molecular weight of 4011.39 Da (4030.40 Da when added Na+) was successfully eluted and collected firstly from its impurities after being recycled for 2 times. In the chromatogram for first cycle, an intense peak upon excitation at 220 nm for [Au3Pz3]C10TEG was observed at retention time of 58 mins, while small peaks due to the presence of impurities was observed in the range between 73 to 85 mins. In the second cycle, the impurities were flushed away before [Au3Pz3]C10TEG was successfully collected at retention time of 170 mins in the third cycle. The columns were a set of polystyrene/divinylbenzene (PS/DVB) JAIGEL-1H and -2.5H connected in series having exclusion limit of 1 X 103 and 2 X 104 in which chloroform was used as the eluent at flow rate of 3.5 mL min-1. As a result, the visual appearance of dark-yellowish [Au3Pz3]C10TEG was successfully purified to give pale-yellowish product. Moreover, differential scanning calorimetry thermogram showed that extra shoulder from impurities at 6.13 °C in the first endothermic peak of [Au3Pz3]C10TEG at 0.76 °C was completely removed. Hence, it can be concluded that size-exclusion chromatography can be used as an effective purification method with much more convenience and small consumption of solvents.